Índice de infestação e fatores de mortalidade do bicudo-do-algodoeiro (Coleoptera: Curculionidae) no semi-árido do sudoeste da Bahia, Brasil - Cardoso, Urbano Pinchemel (2009)
The boll weevil (Anthonomus grandis Boheman, 1843) (Coleoptera: Curculionidae) is a pest that limits the production of cotton, especially in the North East of Brazil. The present study aimed to estimate the infestation index and natural mortality of boll weevil at Caraibas County, located in the semi-arid of the Southwest ofBahia. The experiment was performed using the cultivar BSR Aroeira, at Fazenda Lagoa Seca, in 2006. Weekly evaluations were performed, in five sampling areas 25m2, collecting blossoms fallen on the ground. The infestation was estimated by counting the oviposition punctures and /or the feeding on blossoms, and also by the presence of one of the phases of the boll weevil in the inside. Mortality factors were studied through the dissection of blossoms, estimating predation, parasitism, dissection and disease. The results obtained allowed to conclude that the boll weevil determines high infestation levels in the region. Parasitism, dissection and predation, following this order, determine high rates of real mortality of the pest. Catolaccus grandis Burks, 1954 (Hymenoptera: Pteromalidae) and Bracon sp.(Hymenoptera: Braconidae) are parasitoids of boll weevil reported in sothwestern Bahia, being the first one the predominant species. © 2009, Sociedad Venezolana de Entomología.